Rancang Bangun Sistem Kendali Penyiram Tanaman Jalan Berbasis Kelembaban - Hardi Putra Atyasa; Nugroho Suharto; Azam Muzakhim Imammuddin (Jurnal Jaringan Telekomunikasi, 2021)
Due to the length of the plant area on the road, usually many plants witheror are damaged due to uncontrolled watering. Watering staff on the street usually water the plants periodically. Watering the road plants sometimes causes small congestion and there are parts of the plants that are not watered because it is done manually.The purpose of this research is to create a design of road plant wateringcontrol system humidity-based using a soil moisture sensor, nodeMCU, relaymodule, voltage regulator, and dynamo sprayer. The results of the performance of this device are influenced by the time of the watering schedule and the soil moisture content of the plants.  The results of the design and testing of the tool obtained an automatic plant watering system design and can monitor plant soil moisture with the Thingspeak platform via a web browser. Watering will be done automatically when the time of the watering schedule is entered and the soil moisture is dry. The resultsof the soil sensor readings on soil moisture form an ADC value range of 500 - 900 when the sensor is wet, while 901 - 1023 when the sensor is dry. The delay value for sending data from the soil moisture monitoring system is 0.473 ms at node 1, 0.433 ms at node 2, and 0.245 at node 3. Where the delay value for each node is categorized as good (0 - 150 ms) according to ITUT standards.